Frightful's mountain - George, Jean Craighead, 1919- (New York : Dutton Children's Books, 1999)
As she grows through the first years of her life in the Catskill Mountains of New York, a peregrine falcon called Frightful interacts with various humans, including the boy who raised her, a falconer who rescues her, and several unscrupulous poachers, as well as with many animals that are part of the area's ecological balance.
Keywords: Peregrine falcon -- Juvenile fiction; Peregrine falcon -- Fiction; Falcons -- Fiction; Wildlife conservation -- Fiction; New York (State) -- Fiction